Microbial risk assessment in Vietnam: Translating research and training into policy - Hung Nguyen-Viet; Tuyet-Hanh Tran Thi; Phuc Pham Duc; Ngoc Bich, N.; Mai Huong, B.T.; Hong Nhung, N.; Koottatep, T. (2012)
Until recently, the availability of training in risk assessment in general was very limited in Vietnam, and training in microbial risk assessment (MRA) was not available at all. To fill this gap we developed a training course in MRA by compiling existing MRA trainings, contextualising them, and adapting them to the local context. The resulting course teaches participants the concept of risk analysis, the steps of an MRA and how to implement these steps, as well as risk communication and management. A first one-week training course was successfully held. MRA was also used for assessing health risks related to wastewater reuse in agriculture and food safety in Vietnam. Diverse scenarios of exposure to wastewater when working with wastewater for agriculture, as well as consumption of pork meat were studied to quantify health risk. The results showed that water and vegetables were heavily contaminated with pathogens; risk in the scenarios tested was high and largely exceeded the acceptable level stipulated by WHO. The results also revealed the most critical issues in terms of risk, thereby pointing to topics on which interventions should focus. The findings can serve to improve policies on and practices of waste reuse. MRA has been recognised by health staff, lecturers, researchers, and policymakers at the Ministry of Health (MOH) as a useful tool that provides scientific evidence for decisionmaking and risk management. A book on MRA was published in Vietnamese with support from the Ministry of Health and the World Health Organization (WHO) in Vietnam. It serves as a guideline on MRA, which is a component in Vietnam’s Food Safety Law. The university has adapted the health risk assessment course for undergraduate and graduate public health students. Further initiatives to intensify research on MRA are ongoing, and researchers of the team have been selected to become part of the MOH’s national task force on risk assessment.